Global France, Global French: beyond the monolingual. Issue 1 (April 2017) - Forsdick, Charles
Abstract : The article considers the theme of "Global France, Global French" in the frame of current debates on monolingualism and multilingualism. It explores questions of language use in contemporary France, and focuses on the linguaphobia evident in a number of contemporary ideological, political, social, and cultural contexts. The study suggests that the study of France and French in a global frame requires greater attention to questions of multilingualism and of the contact of the French language and francophone cultures with other linguistic zones. The phenomenon of the "translingual" or "exophonic" writer is presented as a key example of such shifts, and the article concludes with a study of the academician François Cheng, whose writing may be seen as a "translation zone" situated between French and Chinese cultures. The relationship between Cheng and the earlier twentieth-century author Victor Segalen reveals the extent to which the sociolinguistic situations evoked at the opening of the article cannot be limited to the contemporary, and underlines the extent to which an understanding of "Global France, Global French" requires the elaboration of new models of literary, cultural, and historical analysis that are contained neither by the present, nor by the boundaries of a single language or nation. 1